Case report: The lesson from opioid withdrawal symptoms mimicking paraganglioma recurrence during opioid deprescribing in cancer pain - Ruggiero, Elena; Pambuku, Ardi; Caccese, Mario; Lombardi, Giuseppe; Gallio, Ivan; Brunello, Antonella; Ceccato, Filippo; Formaglio, Fabio (Frontiers in Pain Research, 2023)
Pain is one of the predominant and troublesome symptoms that burden cancer patients during their whole disease trajectory: adequate pain management is a fundamental component of cancer care. Opioid are the cornerstone of cancer pain relief therapy and their skillful management must be owned by physicians approaching cancer pain patients. In light of the increased survival of cancer patients due to advances in therapy, deprescription should be considered as a part of the opioid prescribing regime, from therapy initiation, dose titration, and changing or adding drugs, to switching or ceasing. In clinical practice, opioid tapering after pain remission could be challenging due to withdrawal symptoms' onset. Animal models and observations in patients with opioid addiction suggested that somatic and motivational symptoms accompanying opioid withdrawal are secondary to the activation of stressrelated process (mainly cortisol and catecholamines mediated). In this narrative review, we highlight how the lack of validated guidelines and tools for cancer patients can lead to a lower diagnostic awareness of opioid-related disorders, increasing the risk of developing withdrawal symptoms. We also described an experience-based approach to opioid withdrawal, starting from a case-report of a symptomatic patient with a history of metastatic pheochromocytoma-paraganglioma.